Soja transgênica: uma avaliação à luz do ambiente institucional - Souza, José Augusto de (2006)
The controversial caused for genetically modified organism release separate opinions. Notwithstanding exist wade issues on this subject that proves transgenic benefit and many other studies warranting its adoption for economics costs reduction, otherwise there are restless signs of the consumers and environmentalist organizations. This behavior happens because trusty consumers organizations fail in throw ligth on genetically modified food alimentary security. This research is on future position, expectations and strategy for each other actors and they respective partners, what way the contenders will get to restrict this technology or, in other way, improve its adoption. To anticipate the next ten years set about this technology adoption. For instance, has been interviewed ten (10) representative organizations with interest on this subject, at that rate, has been selected four organizations (4) considered favourable and five (5) organizations considered against at its adoption. The applied form was taken face to face with the interviewed, that was build by nineteen (19) questions, six (6) closed questions about interviewed identification and thirteen (13) opened questions right about the subject in progress. After the data analysis, the opposite ideas between the groups favourables and against the transgenic soybean plant, this positions will gain more discussions, because the situations that will happen in the future. We may say that who defends this technology adoption make it in discreet way, while who fight against, do it in strong way